English Terminology in Mobile Legends: A Digital Linguistics Perspective on Player Navigation - Nur Rifda Dzhalzhabillah; Andi Samsu Rijal; Dahniar Dahniar (GLENS: Global English Insights Journal, 2025)
This study examines how English terminology functions within the Mobile Legends: Bang Bang (MLBB) game interface, focusing on its role in player navigation and decision-making. Through qualitative analysis of the game's interface over three weeks, we identified 27 specialized English terms across four key areas: starting menu, hero classifications, positional roles, and battle spell icons. Our findings reveal that these terms form a structured linguistic system rather than random labels, each term serves a specific navigational purpose and helps players make quick strategic decisions during gameplay. The terminology shows interesting linguistic features, including semantic narrowing and the creation of game-specific words, particularly among battle spells. To strengthen our analysis, we gathered feedback from five active MLBB players about their experiences with interface terminology and consulted a linguistics expert to validate our interpretations. The results suggest that MLBB's English terminology operates as a controlled vocabulary that standardizes gameplay communication across different language backgrounds. However, this study primarily analyzed the interface itself rather than extensively exploring how diverse players actually interpret these terms. Future research should include broader player perspectives, especially from users with varying English proficiency levels, to better understand the cognitive processes behind terminology comprehension in multilingual gaming communities.